Highly Efficient Nondoped Near‐Ultraviolet Electroluminescence with an External Quantum Efficiency Greater Than 6.5% Based on a Carbazole–Triazole Hybrid Molecule with High and Balanced Charge Mobility. Issue 21 (30th August 2017) - Xue, Shanfeng; Qiu, Xu; Ying, Shian; Lu, Yuansheng; Pan, Yuyu; Sun, Qikun; Gu, Cheng; Yang, Wenjun
Abstract: Low charge injection and unbalanced carrier transport are unfavorable factors for highly efficient near‐ultraviolet (NUV) electroluminescence (EL) emitters. The construction of weak donor‐ and acceptor‐containing fluorophores has been utilized as a common solution to these issues. Few fluorescent emitters simultaneously exhibiting NUV emission and high/balanced charge‐transport properties have been reported. Herein, a new 1D donor–π–acceptor molecule 9‐(4′‐(4, 5‐diphenyl‐4H‐1, 2, 4‐triazol‐3‐yl)‐[1, 1′‐biphenyl]‐4‐yl)‐9H‐carbazole named PCZTZ consisting of 9‐phenylcarbazole as a donor and 2, 3, 4‐triphenyl‐1, 2, 4‐triazole as an acceptor with a biphenyl π‐bridge is constructed. The backbone‐twisted PCZTZ exhibits not only strong solid‐state NUV fluorescence but also high and balanced hole and electron mobilities (both up to 10 −4 cm 2 V −1 s −1 ), benefiting from the 3D supramolecular H‐bonding network containing strong CH⋯N interactions. Remarkably, a fabricated nondoped light‐emitting diode (OLED) emits 408 nm bright NUV light with a maximal external quantum efficiency of 6.57% and Commission Internationale de L'Eclairage coordinates of (0.17, 0.07). Thus, this OLED is the most efficient NUV OLED reported thus far. These results provide a valuable strategy for the design of highly efficient NUV EL emitters by modulating the linking positions of carbazole and triazole on a biphenyl bridge. Abstract : A near‐ultraviolet (NUV) fluorescent emitter exhibiting a high and balanced carrier mobility of 10 −4 cm 2 V −1 s −1 is achieved using biphenyl‐bridged carbazole and triazole units. The nondoped organic light‐emitting diode (OLED) emits 408 nm bright NUV light with a maximal external quantum efficiency of 6.57% and Commission Internationale de L'Eclairage coordinates of (0.17, 0.07), representing the most efficient NUV OLED reported thus far.